The effect of periodized strength training application on the Korea national team - Song, H.-S.; Park, D.-H.; Jung, D.-S. (International Journal of Applied Sports Sciences, 2009)
The purpose of this study to develop and apply a periodized strength training program for the Korea National Swimming Team. Twelve male swimmers (18.50±2.07 yrs) were adopted 4 times a week for 40 weeks to a periodized strength training program. Assessments for body composition, anaerobic power, agility, maximal strength, and jump height, were performed before (pre) and after 3, and 6 months of resistance training performed 4 days per week. During the periodized resistance training elicited significantly increases resulted inthere were significant increases in fat-free mass; anaerobic power; grip strength; sergent jump; basketball throw; standing long jump; one-repetition maximum (1-RM) squat, bench press, power clean, and dead left. Percent body fat and flexibility decreased significantly decreased after training. The performance level was also elevated as 6 official personal records and 2 Korean records on June, 2006, and 4 personal records, 2 Korean records, and 2 Asian records during Pan Pacific Swimming Championships of Aug. 2006. During Asian Games in December, they established 8 personal, 4 Korean, and 2 Asian records. These results indicated that swimmer-specific periodized strength training may enhanced muscular functions. and performance in elite swimmer.